The case of Synthroid (A) : marketing a drug coming off patent - Tybout, Alice M.; Hennessy, Julie; Fahey, Natalie; Snyder, Charlotte ([London] : SAGE, 2016)
The case tells the story of Synthroid from its development in 1958 as the first synthetic thyroxine molecule to its competition against generic equivalents in 2004. The case introduces students to the pharmaceutical industry, its practices and some of the complexities of pricing and drug choice, with drug manufacturers, insurance companies, physicians, pharmacists and patients all playing a role. It also provides a primer on hypothyroidism, its symptoms and its treatment.
Originally Published in: Tybout, A. M., Hennessy, J., Fahey, N., & Snyder, C. (2013). The Case of Synthroid (A): Marketing a Drug Coming Off Patent (case revised 09/05/2013). 5-312-506(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Drugs -- Marketing -- Case studies; Marketing -- Management -- Case studies